(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The paper is concerned about defining an open library its technology, components, what it will have and provide with respect to the case study of www.openlibrary.org. The paper also concern about application of new technologies in the library which resulted rapid increases and changes in the traditional functions and services of libraries, and the role and nature of works of library profession and the librarianship. The system of information processing, accessing, retrieving, and dissemination had been dramatically changed librarianship. Library had also been transformed into new open source center and open library, virtual library. In such libraries, the librarianship had also been dramatically changed qualities and competencies on the part of library management should also be improved. As well the skills and techniques of the library professionals must be update to cope up with new development in library services.